2004
DOI: 10.1677/joe.0.1810419
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and nitric oxide production in skeletal muscle of type 2 diabetic patients

Abstract: An inflammatory process may be involved in nitric oxide production in skeletal muscle of type 2 diabetic patients. Nitric oxide generation in skeletal muscle was assessed in 14 non-complicated type 2 diabetic patients and in 12 healthy subjects. In samples of quadriceps femoris muscle, endothelial nitric oxide synthase (eNOS), inducible nitric oxide synthase (iNOS), nitrite, nitrate and nitrotyrosine were determined. The macrophage-specific antigen CD163, the T-cell membrane factor CD154 and tumour necrosis fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 33 publications
11
96
4
1
Order By: Relevance
“…Several studies have reported increased inflammatory markers in the skeletal muscle of patients with different conditions including COPD [6,7,[20][21][22][23]. The results of the present study expand this observation by evaluating several inflammatory nucleus of muscle fibre; C: capillary; NE: nucleus of capillary endothelial cell; P:…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have reported increased inflammatory markers in the skeletal muscle of patients with different conditions including COPD [6,7,[20][21][22][23]. The results of the present study expand this observation by evaluating several inflammatory nucleus of muscle fibre; C: capillary; NE: nucleus of capillary endothelial cell; P:…”
Section: Discussionsupporting
confidence: 78%
“…Published by Elsevier Inc. measurement of NO production) are increased in patients with T2DM relative to healthy individuals [1,4]. The actions of NO can be classified as cGMP-dependent actions (such as those related to vascular dilation) or as reactive nitrogen species-mediated (independent of the actions of cGMP).…”
Section: Introductionmentioning
confidence: 99%
“…The cGMP-independent effects are often mediated by nitrosative posttranslational modifications, such as S-nitrosylation, and are thought to play a role in pathological responses, including insulin resistance [5]. Snitrosylation involves the covalent attachment of a NO moiety to protein sulfhydryls and is increased in the skeletal muscle of patients with T2DM [4]. Insulin signaling molecules, such as the insulin receptor, insulin receptor substrate-1 and Akt/PKB, are S-nitrosylated in the skeletal muscle of obese, diabetic mice [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thiobarbituric acid reactive substances (TBARS): Hepatic lipid peroxidation was determined as thiobarbituric acid reactive substances as described by Torres et al [6]. Lipid peroxidation generates peroxide intermediates which upon cleavage release malondialdehyde, a product which react with thiobarbituric acid.…”
Section: Biochemical Determinationsmentioning
confidence: 99%